The role of context as an antecedent for divisiveness in online MBA groups - Picard, Janice M. (Proceedings of the International Conference on Networked Learning, 2008)
While the call for research on how groups learn in networked settings has increased in the past few years (Hodgson and Watland, 2004; McConnell, 2006; Arbaugh and Benbunan-Fich, 2005) further research is needed to examine the relational dynamics found between the structural features of a learning context and how these features influence group dynamics and group work (Carabajal, LaPointe and Gunawardena, 2003). Taking into account broader understandings of the learning context are needed as context plays an important but under scrutinized role in group work and group dynamics. Initial results from a Grounded Theory (Glaser and Strauss, 1967) study examining retrospective accounts of problems undertaking group work in an online MBA suggest that problematic behaviours experienced by group members groups may be sourced within the well spring of operational policies and practices. Tentative findings from the current study suggest that both learners and course tutors behave in ways that privilege competition and competitiveness rather than collectivity, an ideological underpinning of group based practices.